Step 1
Graph
![\begin{gathered} y=(1)/(x) \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pju8xmqxodhml8oiz514jl3nxr87nykfmj.png)
We use values of x= -3 o 3
![\begin{gathered} x=-3 \\ y=-(1)/(3) \\ x=-2 \\ y=-(1)/(2) \\ x=0 \\ y=undefined \\ x=1 \\ y=(1)/(1)=1 \\ x=3 \\ y=(1)/(3) \end{gathered}]()
We will now plot the graph of
![y=(5)/(x+6)](https://img.qammunity.org/2023/formulas/mathematics/college/35otn2rfrs4fqfh00h6yvlgeu1u725xrki.png)
using the points of x=-10,-9,-8,-3,-2,-1,1
![\begin{gathered} x=-3 \\ y=(5)/(-3+6) \\ y=(5)/(3) \\ x=-2 \\ y=(5)/(4) \\ x=-1 \\ y=(5)/(5)=1 \\ x=0 \\ y=\text{ undefined} \\ x=1 \\ y=(5)/(7) \\ x=2 \\ y=(5)/(8) \\ x=(5)/(9) \end{gathered}]()
Together, they will look like this;
Hence, a possible solution is;
![y=(2)/(3),\:x=(3)/(2),\:\quad \:x\\e \:0,\:x\\e \:-6](https://img.qammunity.org/2023/formulas/mathematics/college/np3mvxwss1x0osw1my0yqr6qqy1fd7k9h9.png)
The graphs compare thus;
From the first and second graphs, we can see that they intersect at a point (1.5, 0.667).
Both graphs have the same shape but the following differences:
By looking at the graph we can see that the graph of y=5(x+6) is translated six units to the left with respect to the graph of y=1/x.